Environmental and economic effects of grassroots environmental protection agencies in China: An analysis based on the synthetic control method - Ding, Peiwen; Zhang, Yuhan; Yue, Liping; Zhou, Lei (Frontiers in Environmental Science, 2022)
Grassroots environmental protection agencies are the “last kilometer” of environmental supervision in China, but the effects of these agencies have not received sufficient attention from the economic community. This paper adopts the synthetic control method to estimate the impact of establishing grassroots environmental protection agencies on industrial pollution discharge. The results show that establishing grassroots environmental protection agencies reduces industrial pollution discharge, but the effects are only statistically significant in some regions. In addition, grassroots environmental protection agencies do not significantly impact local economic growth and the economic structure. Grassroots environmental protection agencies generally have problems such as inadequate managerial staff, which may cause the failure in fully executing their functions. The overall promotion of grassroots environmental protection work can hardly be facilitated by the government before these problems are resolved.